Soft Skills of the Third-Year Bachelor of Arts in English Students of Northern Negros State College of Science and Technology - Reynaldo Talita Jr.; Jolito Prietos; Marilyn Maratas (Research Synergy Foundation, 2025)
This study assessed the level of soft skills among third-year AB-English students at Northern Negros State College of Science and Technology during the academic year 2017–2018, to examine their behavioral and developmental implications. Utilizing a descriptive quantitative research design, data were collected through a validated researcher-made questionnaire focusing on eight core soft skills: creativity, time management, conflict management, flexibility, etiquette and good manners, sociability, communication skills, and leadership. Results indicated that the respondents generally possessed high levels of soft skills (grand mean = 4.18), with particularly high ratings in conflict management and etiquette and good manners. No significant differences were found across age and sex, suggesting that these demographic factors did not influence skill levels in this population. From a behavioral perspective, the findings highlight strengths in social interaction and self-management while revealing areas for targeted improvement, such as creativity and flexibility. These insights contribute to behavior-oriented educational strategies by informing curriculum developers and educators on how to design interventions that reinforce essential 21st-century competencies. The results serve as a foundation for an intervention program aimed at enhancing specific soft skills to support students’ academic and professional readiness.